Cochlear Implantation in Patients With Menière's Disease: Does Disease Activity Affect the Outcome?. Issue 9 (October 2020) - Kocharyan, Armine; Mark, Michelle E.; Ascha, Mustafa S.; Murray, Gail S.; Manzoor, Nauman F.; Megerian, Cliff; Mowry, Sarah E.; Semaan, Maroun T.
Abstract : Objective: Menière's disease (MD) is characterized by episodes of vertigo, tinnitus, and sensorineural hearing loss. In the setting of bilateral deafness due to MD alone or contralateral pathology, cochlear implantation (CI) improves hearing. Active MD is characterized by fluctuating auditory symptoms and vertigo; whereas remittance of vertiginous symptoms and severe, permanent sensorineural hearing loss characterizes the inactive disease state. This study evaluates outcomes for MD patients compared with the general CI population and assesses if disease activity affects implant outcomes. Study Design: Retrospective chart review. Setting: Tertiary referral center. Patients: Twenty-four patients with MD that received CI (7 active, 16 inactive, and 1 Probable Menière's), and 24 age-matched controls. Interventions: Cochlear implantation. Main Outcome Measures: Word Recognition Score, Sentence Recognition Score (SRS), and Speech Reception Threshold. Results: Best-aided preoperative and postoperative audiometric data were compared per ear between MD patients and controls and stratified by disease status using descriptive statistics with mixed-effects modeling. Patients with MD derived significantly more benefit from CI than controls when comparing differences between preoperative and postoperative levels for Word Recognition Score (12.2%, p  = 0.0236), SRS (12.8%, p  = 0.0375), and Speech Reception Threshold (−14.4 dB, p  = 0.0188). Active disease status does not negatively impact CI outcomes and patients with active MD may benefit from greater gains in SRS (23.5%, p  = 0.0107). Conclusions: CI provides greater gains in functional hearing for patients with MD compared with age-matched controls. Patients with active MD seem to perform better with respect to SRS following CI than patients with inactive status.